2019
DOI: 10.1080/13102818.2019.1577172
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of endangeredGlehnia littoralis(Apiaceae) in China based on AFLP analysis

Abstract: Genetic diversity studies of endangered plants help to understand the endangering causes and evolutionary history of species. To provide reliable data on the protection of the endangered species Glehnia littoralis, we assessed its genetic diversity and genetic structure based on amplified fragment length polymorphism (AFLP). A total of 127 individuals from 9 wild populations were detected by 10 pairs of AFLP primers. The results showed high levels of genetic diversity in G. littoralis. Ten primer combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The genetic diversity coefficients were higher than or similar to those of other endangered species [9,11,[48][49][50]. This result was consistent with previous studies based on molecular markers and enzyme alleles [51][52][53][54][55]. Genetic diversity is the essence of species evolution and our results showed that G. littoralis has great evolutionary potential, which in turn, implies the contribution of severe habitat destruction on their endangered status.…”
Section: Genetic Structure and Genetic Diversity Analysis Revealed Bysupporting
confidence: 90%
“…The genetic diversity coefficients were higher than or similar to those of other endangered species [9,11,[48][49][50]. This result was consistent with previous studies based on molecular markers and enzyme alleles [51][52][53][54][55]. Genetic diversity is the essence of species evolution and our results showed that G. littoralis has great evolutionary potential, which in turn, implies the contribution of severe habitat destruction on their endangered status.…”
Section: Genetic Structure and Genetic Diversity Analysis Revealed Bysupporting
confidence: 90%
“…AMOVA revealed that a majority of the total genetic diversity resides within populations. Studies on natural populations in China revealed that 77.8% to 84.2% of the total genetic variation occurred within populations (Wang et al 2016;Li et al 2019). These values indicated that the high proportion of the within-population component of genetic variation is a general tendency of the species.…”
Section: Discussionmentioning
confidence: 99%
“…Bands with strong intensity were recorded and classified as present (1) or absent (0) for all accessions to construct a binary data matrix, from which markers lower than 70 bp were excluded. Cluster analysis was carried out using the UPGMA method [11] with the NTSYSpc version 2.2 software package [18] based on Dice's coefficient. Factorial correspondence analysis (FCA) was carried out using GENETIX 4.05 software [19,20].…”
Section: Statistical Proceduresmentioning
confidence: 99%
“…However, genetic diversity and relationships among these two species and their hybrids are still in great need to be unveiled. Genetic diversity and cultivar discrimination studies of non-wood-product forests are currently supported by molecular methods, such as molecular makers and genome sequencing [11]. Amplified fragment length polymorphism (AFLP) technique is a reliable genetic marker with low cost, superior repeatability and high resolution [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation